2022
DOI: 10.3390/ani12182397
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid Extracted from Galla chinensis Supplementation in the Diet Improves Intestinal Development through Suppressing Inflammatory Responses via Blockage of NF-κB in Broiler Chickens

Abstract: The objective of this study was to investigate the effects of adding tannic acid (TA) extracted from Galla chinensis to the diet of broiler chickens on intestinal development. A total of 324 healthy 1-day-old broilers were used in a 42 d study, and divided into two treatment groups at random (six replicates per group). Broilers were either received a basal diet or a basal diet supplemented with 300 mg/kg microencapsulated TA extracted from Galla chinensis. The results showed that dietary supplemented with 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…This study found that jejunal pro-inflammatory mediators (IL-8, IL-1β, iNOS, IFN-γ) were significantly upregulated, the anti-inflammatory mediator (IL-10) was significantly downregulated in broilers with the CCP challenge, and these results suggested that CCP-infected broilers elicited an intestinal inflammatory response in the jejunum. In our study, dietary supplementation with 1000 mg/kg TA significantly diminished pro-inflammatory mediators and elevated anti-inflammatory mediators with CCP challenge, consistent with previous studies [ 43 , 44 , 45 ]. These results suggest that dietary supplementation with 1000 mg/kg TA is beneficial in alleviating intestinal inflammatory responses in broilers co-infected with CCP.…”
Section: Discussionsupporting
confidence: 93%
“…This study found that jejunal pro-inflammatory mediators (IL-8, IL-1β, iNOS, IFN-γ) were significantly upregulated, the anti-inflammatory mediator (IL-10) was significantly downregulated in broilers with the CCP challenge, and these results suggested that CCP-infected broilers elicited an intestinal inflammatory response in the jejunum. In our study, dietary supplementation with 1000 mg/kg TA significantly diminished pro-inflammatory mediators and elevated anti-inflammatory mediators with CCP challenge, consistent with previous studies [ 43 , 44 , 45 ]. These results suggest that dietary supplementation with 1000 mg/kg TA is beneficial in alleviating intestinal inflammatory responses in broilers co-infected with CCP.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, although the protein expression of tight junction (Occludin and Claudin‐2) was not affected by dietary treatment, TA significantly downregulated pro‐inflammatory cytokines (IL‐1β and TNF‐α) expression at the protein level in the jejunum compared to the CON. These results further suggested that TA not only does not cause damage to the intestinal barrier but may also have the potential to decelerate intestinal inflammation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 89 ] found that supplementation with dandelion tannins or soy isoflavones increased the jejunal VH and decreased the jejunal CD. Jing et al [ 90 ] found that adding tannins to broiler diets increased VH/CD and decreased CD. Dietary astragalus polysaccharide supplementation in broilers increased the jejunal VH/CD and decreased the jejunal CD [ 91 ].…”
Section: Discussionmentioning
confidence: 99%